A Complete Perusal of Polluter Pays Principle “Incorporation and Application In India” - Shyamantak Misra1, Hiranmaya Nanda2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Since long it’s a common practice to pay for the destruction and management of destruction caused by one, may it be destruction to property, life, nature etc. However for each kind of destruction there are specific laws and regulations enacted by the parliament. Apart from the laws there are few fundamental truths that act as the base or foundation for a system or in other words some theorems that have numerous special applications across a widespread area which are otherwise known as principles. Polluter pays principle is one of such preventive and remedial theorem applied to people causing environmental damage. This research work focuses on how the polluter pays principle was incorporated in India and emphasizes on its judicial application in various perspectives in India only. This paper starts with the introduction of the principle by “OECD (Organization for Economic Cooperation and Development)” in 1972 and further tracing its movement through the extended version of the principle, being enshrined under principle 16 of the Rio Declaration (UNCED) in 1992, being adopted by the European Community, being adopted as an extension of the rule of Absolute Liability in Torts and finally coming to how it started being applied to, by the Indian Judiciary. This article analyses the judgments pronounced in various cases by the Indian Courts relating to Polluter pays principle.